(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
Nowadays, many young people have to spend a lot of time sitting in a static position, thus resulting in inadequate physical activity. This lack of activity leads to rapid fatigue, decreased work capacity, and posture disorders. Students with weak health should carefully choose methods and means of physical development, considering the disease area. The M. Feldenkrais methodology is designed for a gradual load increase and various exercises. A person should develop an ability to move with minimal effort and maximum efficiency, not through increasing muscle strength but through cultivating an understanding of how the body works. This study aimed to improve posture, self-perception, and well-being among students in a dedicated medical group by using the M. Feldenkrais methodology in physical education classes with an online study format. Thanks to the core principles of this methodology (awareness of movement, neuroplasticity, gradual increasing the complexity of movements, individual approach), physical education trainers can effectively use the proposed exercises in their practice while motivating students to learn by adding something new and interesting. This methodology is also very convenient to apply during the online study process as a form of self-tuition. During classes with Feldenkrais methodology, a playful approach can also be applied to relieve stress and raise the spirits. Furthermore, many coaches use M. Feldenkrais’s approaches in acting and circus art to reveal the linkage between posture, mood, and character. This approach also helps relieve tension. Improvement in posture occurs through awareness of one’s own body in space, strengthening muscles, and developing joint and spine lability. The conducted experiment demonstrates the benefits of using the chosen methodology among students in a dedicated medical group during physical education classes.